The Application of Searching Closest Distance (Travelling Salesmen Problem) Using Ant Colony Optimizatiton Algorithm (ACO) (A Case Study: PT. Nusantara Abadi) - Panji Novantara; Usep Sapari Septiana (JEJARING : Jurnal Teknologi dan Manajemen Informatika, 2022)
Traveling from one place or city to another by considering the efficiency of time and costs requires accuracy in determining the path between the nearby cities. The results need speed and accuracy by using computers. Additionally the service application system is very supportive towards the mobility of users. This condition also happens in the distribution of mineral water. PT. Abadi Nusantara produces several sizes Nalala drinking water circulating in the community, including 19 liter gallon of bottled water, bottled water 500 milliliter, and bottled water 250 milliliter glass. The courier distributors that send the goods, have to consider the time and cost efficiencies when they conduct distribution activities, then sought the shortest distance from their distribution journey. There are various theories of algorithms that can be used to solve the problems of goods distribution or it is often called Travelling Salesmen Problem (TSP), such as brute force algorithm, greedy algorithm, ant colony algorithm, Djikstra, A *, etc. In this thesis, the author chooses one of the algorithms, it is ant colony algorithm to solve the problem of distribution.Keywords : Searching Closest Distance, Traveling Salesman Problem, Ant Colony Optimization Algorithm.